The King’s Decree: Integration of Customary Law and Islamic Law in the Clove Lease Agreement - M. Ali Rusdi,; Pradana, Syafa'at Anugrah; Rustam Magun Pikahulan,; Faisal Nur Shadiq Shabri,; Dirga Achmad, (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2024)
This study examines the impact of the king’s decree on creation of legal products in Iha Village, Maluku. In Iha, legal products are primarily in the form of village regulations that serve as the foundation for government activities within each village. However, Iha distinguishes itself by utilising the king’s decree. This research employs an empirical juridical approach with a socio-legal perspective, which involves examining the legal realities within society and comparing them with applicable positive law. The study finds that the community views the king’s decree as customary decision that must be adhered to, thereby granting the king absolute, as in a case of authority in the execution of the clove lease agreements. Unlike the other village, Iha follows a different procedure for conduction clove lease agreements, as determined by the king’s decree. In addition, the king’s order is also used as a guiding principle for the preservation of local culture and environmental sustainability through the application of local laws in social cultural, and environment contexts. This research can assist the government in formulating draft laws and regulations pertaining to customary law.